Investigating gender differences in the early markers of Autism Spectrum Conditions (ASC) in infants and toddlers. (May 2021) - Barbaro, Josephine; Freeman, Nerelie C.
Highlights: Autistic females are often misdiagnosed and/or diagnosed later than males. Identifying early markers of autism in females is important for accurate diagnosis. There were no gender differences in the behavioural markers of autism in toddlers. The ratio of males to females on the spectrum decreased markedly from 12 to 24 months. Further investigation of early, female-specific, markers of autism are urgently needed. Abstract: Background: Many females with Autism Spectrum Conditions (ASC) are diagnosed later, mis-diagnosed, or missed altogether compared with males, leading to lost opportunities for early supports and services. It is therefore critical that researchers attempt to identify the earliest possible opportunity for females with ASC to be identified and diagnosed. The primary objective of this study was to investigate gender differences in the early signs of ASC in infants and toddlers identified during routine, community-based, developmental surveillance. A secondary aim was to examine gender ratio trends across time. Method: A cross-sectional sample of 197 infants and toddlers (44 female, 153 male) at "high likelihood" for ASC were grouped by autism diagnosis and gender to enable social-communication behaviours to be compared at 18 and 24 months of age. Furthermore, gender ratio trends were examined between 12 and 24 months of age. Results: No gender differences were found across groups at 18–24-months (small samples prohibited analyses at 12-months). However, the ratio of autistic females to males decreased from 1:15 at 12-months to 1:3.2 by 24-months. Conclusions: The results of this study suggest close monitoring of females is required when conducting developmental surveillance for ASC, due to the large gender ratio discrepancy between 12- and 24-months. It is recommended that future studies continue to focus on the early autism phenotype in community-based samples, to assist with modification or development of female specific screening and developmental surveillance tools during infancy and toddlerhood.